Food protein induced enterocolitis syndrome in adults - Kuźmiński, Andrzej; Przybyszewska, Justyna; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Food protein induced enterocolitis syndrome (FPIES) belongs to a group of IgE-independent food allergies. It is the domain of paediatric patients, but it can also occur in adults. In this disease there is a life-threatening risk resulting from the possibility of a severe course of the disease and the development of hypovolemic shock. The disease was first defined in the mid 1970s. Knowledge about this disease is extremely low, we do not know its exact frequency, and the disease itself usually appears between 2 and 7 months of age. FPIES occurs mainly in formula-fed infants, typically 1–4 weeks after formula introduction, very rarely in breastfed infants, but may also develop in adults.